The genus Coenagrion Kirby, 1890 (Odonata: Coenagrionidae) in the Russian part of the Caucasus - Kosterin, Oleg E.; Onishko, Vladimir V.; Ilyina, Elena V.; Chepurnov, Grigory Yu.; Blinov, Alexander G. (Zootaxa, 2024)
Distribution, characters and habitats of Coenagrion spp. in the Russian part of the Caucasus is considered, chiefly by the authors’ own data. There are seven species, of which C. australocaspicum Dumont & Heidari, 1996 is for the first time recorded in Russia (Dagestan), C. ornatum (Selys, 1850) and C. scitulum (Rambur, 1842) in Karachay-Cherkess and Dagestan Republics and C. pulchellum (Vander Linden, 1825) in Dagestan. Coenagrion lunulatum is still known from the territory only by a century-old record by A.N. Bartenev from the highlands of West Caucasus. Keys for identification of the Caucasian species of the puella-group in a broad sense—C. australocaspicum, C. puella (Linnaeus, 1758), C. pulchellum and C. ponticum (Bartenef, 1929)—are provided. Coenagrion ponticum is supposed to be a hybridogenic species resulting from hybridiisation between C. puella and C. pulchellum in the past. Three of the EPIC (exon-primed intron-crossing) molecular markers, AgT, MLC and PRMT, were sequenced from the above mentioned puella-group spp. and C. ornatum, from the territory considered and elsewhere, plus from C. persicum (Lohmann, 1993) from Iran. Coenagrion ponticum thus entered molecular analysis for the first time. Coenagrion australocaspicum appeared divergent from the rest of the group. Coenagrion ponticum appeared inside the cluster of C. pulchellum while C. persicum outside it, so the species status of the former is challenged while that of the latter confirmed. The joint tree showed two clades in C. puella (with no difference in outer characters), one composed of specimens originating from the regions to the south of the Main Caucasian Range and from the Caspian areas of Dagestan including foothills, and the other with specimens from Inner Dagestan (plus one locality in the Caspian-faced foothills), West Caucasus, Western Europe, Ural and West Siberia.